A novel mutation (g.106737G>T) in zone of polarizing activity regulatory sequence (ZRS) causes variable limb phenotypes in Werner mesomelia. Issue 4 (29th January 2014) - Girisha, Katta M.; Bidchol, Abdul Mueed; Kamath, Preeti S.; Shah, Krupa H.; Mortier, Geert R.; Mundlos, Stefan; Shah, Hitesh
<x xml:space="preserve">Abstract</x> Werner mesomelia is characterized by a sequence variation in the specific region (position 404) of the enhancer ZRS of SHH. The phenotype comprises variable mesomelia, abnormalities of the thumb and great toe and supernumerary digits. We describe extensive variation in limb phenotype in a large family and report on a novel sequence variation NG_009240.1: g.106737G>T (traditional nomenclature: ZRS404G>T) in the ZRS within the LMBR1 gene. The newly recognized clinical features in this family include small thenar eminence, sandal gap, broad first metatarsals, mesoaxial polydactyly, and postaxial polydactyly. We provide information on 12 affected family members. We review the literature on how a sequence variation in ZRS may cause such diverse phenotypes. © 2014 Wiley Periodicals, Inc.